Educational leaders and school-based mental health: a social network analysis of knowledge brokerage - Jennifer Turner; Stephen MacGregor; Sharon Friesen (Frontiers in Education)
This study examines the relational dynamics of knowledge brokerage among educational leaders in implementing multi-tiered systems of support (MTSS) for mental health promotion in schools. Recognizing the critical link between student mental health and academic achievement, schools are increasingly expected to provide comprehensive mental health supports. Utilizing social network analysis (SNA), this research explores the information-seeking behaviors of educational leaders within a public school system in British Columbia, Canada. By mapping the relational connections among school and district leaders, the study identifies how these leaders, as knowledge brokers, navigate and influence educational policies and practices related to MTSS. The findings reveal latent interaction patterns that can either facilitate or impede the flow of essential information, highlighting potential areas for strategic intervention. The analysis demonstrates the importance of leadership in fostering collaboration and ensuring the effective integration of mental health initiatives into school communities. Additionally, the study underscores the complex interactions through which knowledge is exchanged and mobilized, emphasizing the need for systems to enhance relational ties and promote collaborative leadership. This research contributes to the scholarship and practice of educational leadership by advancing the understanding of how social networks and knowledge brokerage can support the successful implementation of MTSS.